Relevansi Pendidikan Karakter Ibnu Miskawaih Terhadap Pendidikan Era Modern - khairul huda (JURNAL PENELITIAN KEISLAMAN, 2021)
The purpose of this research is to find out; the concept of character education in the perspective of Ibn Miskawaih, and the relevance of character education in the modern era. This research is library research with content analysis method. The results showed that in shaping character, Ibn Miskawaih implemented four things. However, what is more emphasized is through habituation and practice, because these two methods are carried out continuously and repeatedly. Ibnu Maskawaih emphasizes character education in the world of education which is carried out from an early age and taught through the role of family, education, and society. If with current education the concept of Ibn Miskawaih's character education has relevance to the National Education System Law No. 20 of 2003 as well as the character pillar which aims so that students not only learn to be intelligent, but also have noble personalities and morals.